2017
DOI: 10.4103/ijo.ijo_683_16
|View full text |Cite
|
Sign up to set email alerts
|

Combination of phototherapeutic keratectomy and wavefront-guided photorefractive keratectomy for the treatment of Thiel-Behnke corneal dystrophy

Abstract: Phototherapeutic keratectomy (PTK) has been used to treat anterior corneal dystrophy but may cause hyperopic shift or corneal high-order aberration. We describe the successful treatment of a case of a 43-year-old female with Thiel–Behnke corneal dystrophy, using PTK followed by wavefront-guided photorefractive keratectomy (PRK). The patient had high corneal aberration and hyperopic shift after PTK in both eyes. The corneal surface regularity index and surface asymmetric index increased after PTK and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similar to RBCD, PTK is a good treatment modality to remove corneal deposits and improve vision. As mentioned, it can induce hyperopic shift and less commonly cause delayed re-epithelialization, corneal haze and scarring, and irregular astigmatism secondary to a decentred ablation zone or uneven ablation due to pathological corneal opacities [ 32 , 33 , 34 ]. These side effects are more common with deeper ablations [ 34 ].…”
Section: Thiel–behnke Corneal Dystrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to RBCD, PTK is a good treatment modality to remove corneal deposits and improve vision. As mentioned, it can induce hyperopic shift and less commonly cause delayed re-epithelialization, corneal haze and scarring, and irregular astigmatism secondary to a decentred ablation zone or uneven ablation due to pathological corneal opacities [ 32 , 33 , 34 ]. These side effects are more common with deeper ablations [ 34 ].…”
Section: Thiel–behnke Corneal Dystrophymentioning
confidence: 99%
“…Hsiao et al described a variation to standard PTK that aimed at reducing the post-PTK hyperopia by using combined wavefront-guided photorefractive keratectomy (PRK) combined with excimer laser PTK in one TBCD patient [ 33 ]. The treatment was successful and resulted in significant vision improvement in both eyes.…”
Section: Thiel–behnke Corneal Dystrophymentioning
confidence: 99%
“…In adults, PTK has been used extensively for the treatment of corneal scarring, corneal dystrophies/degenerations, and recurrent corneal erosions [18, 19]. These various PTK techniques have used broad-beam ablations [19], intraoperative masking agents [20], focal [21] and selective zonal [22] ablations, dual ablations [23], transepithelial methods [24], wavefront-guided ablations [25], topography-guided ablations [26], and wavefront-optimized ablations [27]. However, there are relatively few studies in which any PTK technique has been reported for its use in the pediatric population [2832], especially using more advanced techniques which take the advantage of novel imaging modalities.…”
Section: Introductionmentioning
confidence: 99%